Effects of Antidiabetic Drugs on Endothelial Function in Patients With Type 2 Diabetes Mellitus: A Bayesian Network Meta-Analysis - Wang, Yuhan; Yao, Mingyan; Wang, Jincheng; Liu, Hongzhou; Zhang, Xuelian; Zhao, Ling; Hu, Xiaodong; Guan, Haixia; Lyu, Zhaohui (Frontiers in Endocrinology, 2022)
Background: The changes of endothelial function in type 2 diabetes mellitus (T2DM) patients are closely associated with the development of cardiovascular disease (CVD). However, it is still unclear whether commonly used antidiabetic drugs can improve endothelial function. Flow-mediated dilation (FMD) is a noninvasive tool for evaluating endothelial function, which typically examines changes in the brachial artery diameter in response to ischemia using ultrasound. We performed a network meta-analysis (NMA) to explore the associations between changes in endothelial function and antidiabetic drugs by evaluating FMD in T2DM patients. Methods: We systematically searched several electronic databases for randomized controlled trials (RCTs) published from inception until September 24, 2021, with no language restriction. The primary outcome was FMD in all studies, and we performed subgroup analysis on FMD in T2DM patients without CVD. NMA was performed to calculate the mean differences (MDs) with 95% confidence intervals (CIs). Results: From the 517 candidate articles identified in the initial search, 31 RCTs involving 1875 participants were eventually included in the analysis. In all studies, glucagon-like peptide-1 receptor (GLP-1R) agonists (MD = 4.15 [1.55–6.73]), metformin (MD = 2.05 [0.03–4.06]), and dipeptidyl peptidase-4 (DPP-4) inhibitors (MD = 1.93 [0.27–3.52]) produced improvement of FMD compared to other treatment (OT). GLP-1R agonists (MD = 3.47 [1.03–5.92] and MD = 3.54 [0.82–6.27]) showed significantly greater improvements in FMD in pairwise comparisons with sulfonylureas and placebo. In studies of T2DM patients without CVD, GLP-1R agonists (MD = 4.69 [1.93–7.42]), metformin (MD = 2.53 [0.32–4.69]), and DPP-4 inhibitors (MD = 2.43 [0.66–4.12]) produced improvements in FMD compared to OT. GLP-1R agonists (MD = 2.17 [0.06–4.28], MD = 3.33 [0.65–6.03], and MD = 3.70 [0.84–6.68]) showed significantly greater improvements in FMD in pairwise comparisons with metformin, sulfonylureas, and placebo. Conclusion: In T2DM patients, both GLP-1R agonists, metformin, and DPP-4 inhibitors have favorable effects to improve FMD in T2DM patients. In T2DM patients without CVD, GLP-1R agonists also had a greater effect to improve FMD than metformin and sulfonylureas. These suggested that GLP-1R agonists are associated with significantly improved endothelial function in T2DM patients.